Kajian penerapan metode praktikum secara efesien pada materi korosi di SMA YPPK st. Thomas aquino Kaimana - Theresia N. R. Boce; Emma Juline Pongoh; Rymond Jusuf Rumampuk (Oxygenius Journal Of Chemistry Education, 2019)
The application of practicum methods efficiently is able to help educators to achieve success in the chemistry learning process. This study aims to determine student learning outcomes in corrosion material through the learning process by applying the practicum method. This research was conducted in the odd semester of the 2018/2019 academic year for students of class XII Science in YPPK High School St. Thomas Aquino Kaimana. The sample used in this study is all students of class XII IPA St. Thomas Aquino Kaimana. The indicator used in this study is individual success, that is, if the student has reached the value of 75. Analysis of the data in this study used the percentage completeness learning technique based on the results of the indicators obtained. The results showed that from the initial test of student learning outcomes had not reached completeness (value 75) with the percentage of completeness of learning outcomes of 0% and from the final test the results of student learning had reached a grade (value> 75) with a percentage of completeness of learning outcomes of 100%. Based on the results of this study it can be concluded that the learning outcomes of students in the subject matter of corrosion with the practicum method were increased.